Effect of Water Stress on Yield and Water Productivity of Drip Irrigated Cassava (Manihot esculenta) in Ibadan, Nigeria - Awoyode, A. F.; Ewemoje, T. A.; Adeboye, O. B. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2023)
Cassava (Manihot esculentus) is an important staple tuber crop in many regions of Africa. It is a cash crop with wide domestic and industrial applications. Hence, there is a need to sustain its production during water scarcity. This study examined the effect of available soil moisture on phenological parameters and drought resistance of four improved varieties of cassava, TMS (30572, 980505, 920326 and 090581) using water productivity. The water management regimes (T75 maximum water regime - 75% of Evapotranspiration (ET); T50, 50% ET, T25 - 25% ET and Control, zero irrigation). The varieties and water regimes were applied and the treatment was arranged using a Latin Square design with four replications. Lynne's model was used in calculating the irrigation water requirements. The amount of water supplied to each treatment varied with the duration of irrigation. The results show that TMS 980505 at T75 had the highest tuber, stem and leaf productivities of 2.76, 1.66 and 2.05 kg m-3 respectively while TMS 30572 on the control regime had the least tuber, stem and leaf productivities of 0.16, 0.21 and 0.21 kg m-3 respectively. The TMS 980505 can be grown in regions where substantial crop water requirements for cassava could be met during the dry season through irrigation while TMS 090581 could be grown in water-scarce regions with a guaranteed 370 mm of water with an average yield of 4.5 t ha-1. The TMS 090581 at T75 had the highest plant height of 128 cm while TMS 30572 on control had the least height of 56 cm.  TMS 920326 at T75 had the highest stem girth of 21.4 mm while TMS 30572 at T50 had the least stem girth of 10.7 mm. Therefore, full irrigation is recommended for the cultivation of TMS 980505 during the dry season. The TMS 090581 has the highest drought resistance. Therefore, it is recommended for cultivation in water-scarce regions.